The effectiveness of technology‐based interventions for smoking cessation: An umbrella review and quality assessment of systematic reviews. (6th April 2021) - Mersha, Amanual Getnet; Bovill, Michelle; Eftekhari, Parivash; Erku, Daniel Asfaw; Gould, Gillian S.
Abstract: Issues: With the advancement and rapid increase in the public's interest in utilisation of Internet and mobile phones, technology‐based interventions are being implemented across a range of health conditions to improve patient outcomes. The aim of this review was to summarise findings from systematic reviews that evaluated the effectiveness of technology‐based smoking cessation interventions and to critically appraise their methodological qualities. Approach: An umbrella review was conducted using studies identified from a comprehensive literature search of six databases and grey literature. All included systematic reviews were checked for eligibility criteria and quality using the Assessment of Multiple Systematic Reviews tool. The level of evidence for each intervention category was assessed, citation matrices were generated and corrected covered area was calculated. Key Findings: Five systematic reviews with a total of 212 randomised controlled trials and 237 760 participants were included. Fourteen intervention approaches were identified and classified into three categories: stand‐alone web‐based; stand‐alone mobile phone‐based and multicomponent interventions. Incorporating web and/or mobile‐based interventions with face‐to‐face approach improved the rate of smoking cessation. However, there was no consistent evidence regarding the effectiveness of stand‐alone Internet or mobile‐based interventions. Implications: Policymakers are recommended to develop strategies that enable health professionals to integrate these approaches with face‐to‐face smoking cessation support. Health professionals are recommended to be trained and equipped for online and mobile‐based interventions. Conclusion: Adding technology‐based intervention to face‐to‐face smoking cessation support improves smoking cessation. Further research is needed to evaluate stand‐alone web‐based and mobile phone‐based interventions.